The Views of High School Students During The Covid-19 Period on Learning Mathematics - Rohati Rohati; Marlina Marlina; Khidayatul Isna (IJECA (International Journal of Education and Curriculum Application), 2021)
The Covid-19 pandemic has reshaped people's lives, attacking the Indonesian state and spreading throughout the world. This condition necessitates that all teaching and learning take place online. However, students continue to face numerous obstacles during implementation. The purpose of this study is to ascertain the responses provided by students during the performance of online mathematics learning and to ascertain their suggestions and desires for the subsequent semester's implementation of mathematics learning. The study used a descriptive qualitative research approach to select 373 students as research subjects. The data collection method was a google form, and students were asked to provide an open response regarding their wishes and expectations for online mathematics education in the following semesters. The findings indicated that students expected face-to-face instruction to facilitate direct interaction with teachers and other students. Additionally, students desire to improve their ability to learn and organize their learning more effectively. Additionally, students express their opinions and responses about online mathematics education, including the level of mathematics material and technology (utilization of the zoom platform). Additionally, deadlines for extending tasks, the use and utilization of instructional videos, and the explanation of mathematics material are more comprehensive. Teachers can use the findings of this research to evaluate mathematics learning in order to improve their classroom instruction, and other teachers can do the same thing.